An airfield in the Northern Cape landscape: exploring meaningful place-making to establish a gliding club that relates with Douglas - Van den Berg, H. F. (University of the Free State, 2020)
The inspiration for this dissertation comes from a personal love for my hometown, Douglas, located in the Northern Cape, 100 km south-west of Kimberley, South Africa. My curiosity drove me to explore what a contemporary architectural language might look like in such a rural town. Also, I wonder what an architect’s way of thinking can contribute to such a community. The exploration of the spirit of place of Douglas provides the parameters for this design dissertation; to create a space that becomes a meaningful place that celebrates the complexity of Douglas. The uniqueness of this rural town lies in the fact that it is an oasis in contrast to the surrounding cosmic landscape. Annually, people travel to Douglas to engage in the adventurous act of gliding. The proposed site, the Douglas airfield, located 3 km from the town on the farm Backhouse, becomes a threshold that introduces people from different backgrounds to the dwellers of Douglas through this technologically sophisticated sport. The aim of the study is to develop the airfield so that it can facilitate the World Gliding Championships (Fédération Aéronautique Internationale, 2019: online), which could stimulate growth, allowing the opportunity to present the uniqueness of this this place, and the people who settle here, on a global scale. I will first provide an overview of Douglas to orientate the aims of the dissertation. A deeper investigation will follow, allowing a broader understanding of the place and the people who dwell there. Exploring the historical narratives and the complex traces of the dwellers of and travellers through Douglas will allow the creation of a place with which both the dweller of and traveller to Douglas can identify.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2020
Keywords: Architect - Landscape - Northern Cape; Airfield - Northern Cape; Architecture - Douglas - Northern Cape; Douglas airfield